Emergency Service Application for Traffic Accidents in Yogyakarta Area Using Location Based Service Method - Aqza Anugrah, Muhammad; Sri Utami, Wahyu (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
Every hour, three people die in Indonesia due to traffic accidents. This staggering toll is largely driven by human error. A dire need for immediate action insists to provide a better emergency response system before it is getting worse. This research aims to design and develop an integrated emergency application connecting users with multiple service providers, and to assess its impact on improving response times and reducing traffic accident casualties, contributing to safer urban environments and better public health outcomes. The study uses diagrams to model user interactions and system components, including police, hospitals, and firefighters. A structured framework guides the research from data collection to system implementation and testing, ensuring the system enhances emergency response times. This research reveals that the emergency application was designed to provide quick access to police, hospital, and fire fighter department services. The homepage allows users to select a service and access either a phone number list or the nearest location via Google Maps. Testing confirmed successful navigation, phone number display, and map integration in both offline and online modes. Black Box Testing showed that all core features, including menu navigation and call redirection, functioned as expected. The app is intended to enhance emergency response times by providing immediate, efficient access to critical services.